A Study on Experimental Investigation on Bio Aerosols - Indira S Jain; Pooja Singh (International Journal of Scientific Research in Civil Engineering, 2024)
Bioaerosols consist of aerosols originated biologically such as metabolites, toxins, or fragments of microorganisms that are present ubiquitously in the environment. International interests in bioaerosols have increased rapidly to broaden the pool of knowledge on their identification, quantification, distribution, and health impacts (e.g., infectious and respiratory diseases, allergies, and cancer). However, risk assessment of bioaerosols based on conventional culture methods has been hampered further by several factors such as: (1) the complexity of microorganisms or derivatives to be investigated; (2) the purpose, techniques, and locations of sampling; and (3) the lack of valid quantitative criteria (e.g., exposure standards and dose/effect relationships). Although exposure to some microbes is considered to be beneficial for health, more research is needed to properly assess their potential health hazards including inter-individual susceptibility, interactions with non-biological agents, and many proven unproven health effects (e.g., atopy and atopic diseases).
Keywords: Bioaerosols; Health; Environment; Sampling; Standards; Risk